A real-coded genetic algorithm for optimizing the damping response of composite laminates. (March 2018) - Pathan, M.V.; Patsias, S.; Tagarielli, V.L.
Highlights: A new real-coded, constrained genetic algorithm is developed and tested. The algorithm provides a good mix of programming simplicity and computational efficiency. The algorithm is employed to optimise damping of a FRP laminate comprising viscoelastic inserts. Damping can be increased by one order of magnitude by placing viscoelastic inserts to promote shear. Abstract: We develop a real-coded constrained genetic algorithm (GA) and assess its performance for the case of selected classical optimisation problems. The proposed GA uses a roulette selection method, BLX-α crossover operation, non-uniform mutation along with single elitist selection at every generation. The GA is then applied, in conjunction with the finite element (FE) method, to optimise the damping response of a laminate comprising unidirectional composite laminae and viscoelastic damping layers. Modal loss factors are maximised against the constraints of given structural stiffness and mass.